Development and Validation of a New LC-MS/MS Method for the Assay of Plasmatic Peripheral Short- and Medium-Chain Fatty Acids for Metabolomics Applications - Lenard Farczadi; Laura Barcutean; Smaranda Maier; Rodica Balasa; Silvia Imre (Metabolites)
Background: Short-chain fatty acids (SCFAs) and medium-chain fatty acids (MCFAs) are human metabolites which are involved in various biochemical processes and can offer valuable insights and information on various pathological and metabolic issues of patients. Accurate, precise, high-performance bioanalytical methods are important tools in both research and diagnostics of many pathologies, with LC-MS being the most frequently used methodology in modern metabolomics studies. Methods: The current paper describes a complete LC-MS/MS methodology for the accurate quantification of total plasmatic SCFA concentrations in humans using high-resolution QTOF mass spectrometric detection, including sample cleanup, preparation, and derivatization. Results and Conclusions: The method was validated with regard to all relevant parameters (selectivity, sensitivity, accuracy, precision, linearity, recovery, carryover, and reproducibility of sample preparation) according to the current applicable guidelines and tested in an in vivo study to quantify peripheral SCFAs in human patients as biomarkers for gut–brain axis disruption.